2015
DOI: 10.1590/s0034-8910.2015049005549
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predicting factors of falls of older inpatients

Abstract: OBJECTIVE To estimate the incidence and predicting factors associated with falls among older inpatients.METHODS Prospective cohort study conducted in clinical units of three hospitals in Cuiaba, MT, Midwestern Brazil, from March to August 2013. In this study, 221 inpatients aged 60 or over were followed until hospital discharge, death, or fall. The method of incidence density was used to calculate incidence rates. Bivariate analysis was performed by Chi-square test, and multiple analysis was performed by Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
2
26

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 24 publications
3
39
2
26
Order By: Relevance
“…It was further stated that each of the known causes should be identified. In hospital, lower urinary tract symptoms of urinary urgency, incontinence, frequency and nocturia are known risk factors for falls among older adults . Nocturia is not routinely identified on hospital admission.…”
Section: Introductionmentioning
confidence: 99%
“…It was further stated that each of the known causes should be identified. In hospital, lower urinary tract symptoms of urinary urgency, incontinence, frequency and nocturia are known risk factors for falls among older adults . Nocturia is not routinely identified on hospital admission.…”
Section: Introductionmentioning
confidence: 99%
“…There are few data on adult inpatient falls in Brazil, and most of the studies conducted on the issue restricted their focus to elderly patients. In a study carried out in three large general hospitals in a single state in Brazil, the rate of fall among elderly inpatients was 12.6 per 1,000 patients a day (Abreu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The PNSP is composed of six goals, among them falls prevention which is defined by WHO as an "event in which the person inadvertently falls to the ground, floor or lower levels, excluding the intentional alteration of the position for resting on furniture, walls or other objects" (1)(2)(3) . Brazilian studies developed in hospital environments where the rate of falls was evaluated found that they ranged from 1.37 to 12.6 per 1,000 patients/day (4)(5) . These rates are related to the characteristics of the hospital institutions, as well as the patients.…”
Section: Introductionmentioning
confidence: 99%